Efficacy of High Sensitivity C- Reactive Protein, Lipoprotein A and Troponin I levels in Predicting Cardiovascular Disease Severity on Coronary Angiogram- A Prospective Study - Khobragade, Abhishek; Porwal, Sanjay; Patted, Suresh; Ambar, Sameer; MR, Prasad; Metgudmath, Vijayanand; Hesarur, Vishwanath (Cardiology and Cardiovascular Medicine, 2024)
Background: Cardiovascular diseases (CVDs) continue to be the primary cause of death globally, significantly contributing to health deterioration and increased healthcare expenses. Annually, CVDs are responsible for more deaths than any other disease, causing approximately 17.9 million deaths, which equates to around 31% of global mortality. This study investigated the efficacy of high sensitivity c- reactive protein (hs-CRP), Lipoprotein A levels (Lipo A), and Troponin I (Trop I) levels in predicting CVD severity on coronary angiogram Materials and Methods: This prospective observational study included 211 patients aged 18 years and above, with a diagnosis of acute coronary syndrome (ACS), who visited the Department of Cardiology. A detailed history was recorded, and laboratory investigations included hs-CRP, Lipo A, Trop I, and Lipid Profile, and all the patients were subjected to coronary angiography. Coronary angiogram was studied and the severity of CVD was noted, based on SYNTAX I and II. Results: The mean age of study patients was 62.82±10.17 years, with age ranging from 34 to 89 years, and the majority being male (70.1%). 78.7% of patients were hypertensive and 71.6% were diabetic. Most common signs and symptoms were chest pain (96.2%) and dyspnoea (87.2%). The higher levels of mean hs-CRP, Lipo A, Trop I, and LDL were significantly associated with the severity of CVD on coronary angiogram (p<0.001). Conclusion: Higher levels of hs- CRP, Lipo A, and Trop I can be a reliable predictor of the severity of CVD on coronary angiogram.